A Systematic Review of Mental Health Nurses' Perceptions of Their Professional Identity - Kelly, Peter (International Journal of Mental Health Nursing, 2025)
Evidence suggests that moving from specialist to generic nurse education, as is proposed in the United Kingdom and as has already happened in countries such as Australia, leads to a reduction in the quality of mental health nurse education and a weakening of mental health nurse professional identity. Meanwhile, research has found that mental health nurse professional identity is already complex because of the discipline's multifaceted but objectively ambiguous role. The present qualitative systematic review aimed to explore mental health nurses' perceptions of their professional identity. It was conducted in the form of a thematic analysis of qualitative data and was compliant with PRISMA reporting guidelines. Six databases (CINAHL Ultimate, EBSCO Medline, APA PsycInfo, APA PsycArticles, PubMed and SCOPUS) were searched in April and May 2024. The literature search yielded a total of n = 3710 studies. Following a process of screening using Covidence and quality appraisal using the CASP tool, a total of n = 23 peer-reviewed qualitative studies were selected for inclusion. Five themes emerged: (1) Professional identity formation, (2) The attributes of mental health nurses, (3) The mental health nurse role, (4) The unique skills and knowledge of mental health nurses and (5) Professional identity and the future of mental health nursing. This systematic review concluded that mental health nurses recognise their profession as being complex and difficult to describe; however, they remain positive and committed to their roles, recognising that the uniqueness of mental health nursing may become its defining strength.
PUBLISHED
https://doi.org/10.1111/inm.70137
Keywords: Inclusive Society; International Integration; Leadership in nursing; Mental health nursing; NURSING EDUCATION; Nursing; Mental Health/Psychosocial disability; Carers; Education; Health; Policy